Pentingnya Menjaga Kebersihan Lingkungan untuk Kesehatan Masyarakat di Desa Doulu Kabupaten Karo - Rizki Bastanta B. Manulu; Aser Paul Nainggolan; Hasiholanta S Sinurat; Efranta Natanael Karo-Karo; Juniedi P Ompusunggu (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
Environmental cleanliness is people's constant desire to achieve life. It is necessary to carry out activities that encourage people to choose a healthy lifestyle. One way to maintain environmental cleanliness is through socializing environmental cleanliness with discussions located in Doulu Village, Karo Regency, North Sumatra Province. Activities in the PKM include socializing the importance of keeping the surrounding environment clean and physical fitness training. The aim of implementing this cleanliness outreach program is motivated by the local community's lack of awareness in disposing of waste properly and also maintaining health. The method used is to conduct interviews with local communities to identify the main problems in the area. As a result, the people around Doulu Village, Karo Regency are increasingly aware of implementing clean and healthy living habits and being able to differentiate between types of waste, as well as maintaining physical fitness through healthy exercise.